KNOWLEDGE AND ROLE OF COMMUNITY IN THE ADMINISTRATION OF NATURAL RESOURCE CONSERVATION OF NAM PHONG NATIONAL PARK - Phetsuk, Chatbuncha; Lowatcharin, Grichawat (Journal of MCU Nakhondhat, 2023)
This research aims to: 1) study the level of knowledge and skill of natural resource conservation management 2) study the role of communities and factors influencing the role of the community in the management of natural resource conservation in Nam Phong National Park, and 3) get the results of conservation administration of Nam Phong natural resources through community networks. This research is quantitative. The population were residents of three communities located on the route to the Nam Phong National Park Office in Khon Kaen Province. Data were collected with questionnaires from 202 residents. The research tools were questionnaires. The statistical data used in the study include percentages, averages, and standard deviations, and descriptive statistical data are used to analyze the data. The research results show that: 1. The knowledge and understanding of the communities around Nan Phong National Park in Khon Kaen Province are divided into two parts: (1) The general information is mainly for women, aged between 41 and 50, with a high school education, employment, and a higher average monthly income of 15,000 baht; most of them have lived in the community for more than 15 years, and they are not volunteers for national parks and wildlife protection. (2) Overall understanding of natural resource conservation and management in Nam Phong 2. The role of communities in the protection and management of natural resources in communities around Nam Phong National Park 3. The results of natural resource conservation in Nam Phong through community networks; the role of community networks in natural resource conservation and management will have the greatest impact on management, and they can reduce conflicts and affect the effectiveness of management. Cooperation between communities and national parks will help protect natural resources and community lifestyles.